Study on The Production of Local Microorganisms (MOL) as a Starter for Cattle Feed Fermentation - Aisyah, Nurul; Irwan, Muh; Purnomo, Nurul (Jurnal Ilmu Dan Teknologi Peternakan Indonesia (JITPI) Indonesian Journal of Animal Science and Technology), 2025)
This study aims to determine the impact of various carbohydrate sources on the temperature, liquid volume, color, and pH of local microorganisms (MOL). The research employed a descriptive and quantitative approach, using a completely randomized design (CRD) with three treatments and six replicates. The treatments included potato (P1), stale rice (P2), and cassava (P3). Parameters measured were temperature, liquid volume, color, and pH. Results showed that the type of carbohydrate source significantly affected (P < 0.01) temperature, liquid volume, and pH. The highest temperature was observed in the P3 treatment, followed by P2 and P1. The greatest liquid volume occurred in P3, then P2 and P1. Treatment P1 had the highest pH level, followed by P2 and P3. The color of the fermented liquid remained similar to that of the raw materials. The findings indicated that the P3 treatment, involving cassava, produced optimal fermentation results, characterized by low pH levels, suitable temperatures, stable liquid volumes, and color closely resembling the original ingredients.